2017
DOI: 10.1002/anie.201708190
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Ligand Shell Morphology during Ligand Exchange Reactions on Gold Nanoparticles

Abstract: Ligand exchange reactions are used to achieve nanoparticles coated with a mixture of ligand molecules. Currently, nothing is known on the evolution of the morphology of the ligand shell during the reaction. Here, we use a recently developed method (based on MALDI-TOF) to follow the evolution of the ligand shell composition and morphology during the reaction. We observe the expected evolution in composition and we find that the ligand shell starts as a random mixture and gradually evolves towards a patchy morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…29 The kinetics and evolution of the ligand shell morphology in thiol-for-thiol exchange reactions were recently studied in great detail. 30 An alternative is the synthesis of AuNPs with a more labile intermediate capping agent to facilitate the exchange. The use of AuNP protectants such as citrate, 31 phosphine, 32,33 4-(N,N-dimethylamino)pyridine (DMAP), 34,35 dioctylamine (DOA), 36 and tetraoctylammonium bromide (TOAB) 37 allows us to separate the synthesis of the AuNP core and the formation of a tailored ligand shell via a thiol-for-agent ligand-exchange procedure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…29 The kinetics and evolution of the ligand shell morphology in thiol-for-thiol exchange reactions were recently studied in great detail. 30 An alternative is the synthesis of AuNPs with a more labile intermediate capping agent to facilitate the exchange. The use of AuNP protectants such as citrate, 31 phosphine, 32,33 4-(N,N-dimethylamino)pyridine (DMAP), 34,35 dioctylamine (DOA), 36 and tetraoctylammonium bromide (TOAB) 37 allows us to separate the synthesis of the AuNP core and the formation of a tailored ligand shell via a thiol-for-agent ligand-exchange procedure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…dPET-DDT nanoparticles were synthesized using a different approach, i.e., ligand exchange reaction. It has been demonstrated that ligand exchange reactions at room temperature often leads to nanoparticle morphologies that are not at the equilibrium 26 , 27 . After the ligand exchange reaction and thorough purification, the nanoparticles were annealed in pure toluene for 24 h at 50 °C to allow for the morphology to equilibrate.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticle synthesis and purification. Mixed ligand gold NPs were synthesized using the Stucky protocol 56 followed by ligand exchange reaction as reported previously 57 . First, homo-alkanethiol protected NPs were synthesized as following: 123 mg triphenylphosphinegold (I) chloride and 0.25 mmol alkanethiol ligand (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…As the size of a NP is always the primary question in its characterization, we first focus on demonstrating the sensitivity of SANS to the dimension of both the metal core and organic shell. Two series of gold NPs were synthesized according to previous literature 37,56,57 . First, three MNPs with different core sizes but the same ligand shell coating were produced using a ligand exchange protocol 56,57 .…”
Section: Dimensional Informationmentioning
confidence: 99%